2006
DOI: 10.4049/jimmunol.176.2.790
|View full text |Cite
|
Sign up to set email alerts
|

Early Preplasma Cells Define a Tolerance Checkpoint for Autoreactive B Cells

Abstract: Ab-secreting plasma cells (PCs) are the effectors of humoral immunity. In this study, we describe regulation of autoreactive B cells specific for the ribonucleoprotein Smith (Sm) at an early pre-PC stage. These cells are defined by the expression of the PC marker CD138 and normal levels of CD19 and B220. They are present at a high frequency in normal mouse spleen and bone marrow, are Ag dependent, and are located predominantly along the T cell-B cell border and near bridging channels. Anti-Sm pre-PCs also occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
88
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(99 citation statements)
references
References 56 publications
(61 reference statements)
10
88
1
Order By: Relevance
“…Autoreactive B cells from SW HEL X HEL 2X mice may have an intrinsic impairment preventing the differentiation into IgG plasma cells due to chronic exposure to the autoAg, especially at the GC level. The existence of a tolerance checkpoint between the GC and plasma cell compartments has been previously suspected in other transgenic mice and in FcRIIb −/− mice [44][45][46].This study reveals control mechanisms that are effective during chronic infection even when self-reactive B cells are activated and pushed to SHM in GCs. Thereby, we provide an explanation for the low prevalence of pathogenic IgG autoAbs in healthy individuals' sera.…”
supporting
confidence: 52%
“…Autoreactive B cells from SW HEL X HEL 2X mice may have an intrinsic impairment preventing the differentiation into IgG plasma cells due to chronic exposure to the autoAg, especially at the GC level. The existence of a tolerance checkpoint between the GC and plasma cell compartments has been previously suspected in other transgenic mice and in FcRIIb −/− mice [44][45][46].This study reveals control mechanisms that are effective during chronic infection even when self-reactive B cells are activated and pushed to SHM in GCs. Thereby, we provide an explanation for the low prevalence of pathogenic IgG autoAbs in healthy individuals' sera.…”
supporting
confidence: 52%
“…Both SLE patients and lupus-prone mice have alterations in their B-cell subsets, such as an increased proportion of plasmablasts and/or plasma cells, GCs, etc., [39][40][41][42][43] which reflects the disturbed differentiation of B cells in SLE patients and lupus-prone mice. In the present study, we found that compared with wild-type mice, CD138 1 plasmablasts/plasma cells and B220 1 GL-7 1 GC B cells are increased in MRL/lpr mice and are CD180-negative.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the 2-12H transgene in MRL/lpr mice increases the prevalence of the anti-Sm response, accelerates disease, and leads to higher serum anti-Sm levels [65]. Sm-specific B cells from 2-12H mice are arrested at the pre-plasma cell stage, while B cells from the 2-12H/MRL/lpr mice bypass this checkpoint and become activated [93].…”
Section: A Short History Of Smmentioning
confidence: 99%
“…Expression of the 2-12H transgene in MRL/lpr mice increases the prevalence of the anti-Sm response, accelerates disease, and leads to higher serum anti-Sm levels [65]. Sm-specific B cells from 2-12H mice are arrested at the pre-plasma cell stage, while B cells from the 2-12H/MRL/lpr mice bypass this checkpoint and become activated [93].The presence of class-switched autoantibodies in MRL/lpr mice suggests a breakdown in tolerance within the adaptive immune response. In MRL/lpr mice where somatic hypermutation and isotype switch recombination are blocked (AID −/− ), lupus-like symptoms such as glomerulonephritis, proteinuria, and immune complex deposition are ameliorated [94].…”
mentioning
confidence: 99%